Effect of DNMT3A polymorphisms on CpG island hypermethylation in gastric mucosa - Hikaru Takano; Tomoyuki Shibata; Masakatsu Nakamura; Naoko Sakurai; Tasuku Hayashi; Masafumi Ota; Tomoe Nomura-Horita; Ranji Hayashi; Takeo Shimasaki; Toshimi Otsuka; Tomomitsu Tahara; Tomiyasu Arisawa (BMC, 2020)
Abstract Background CpG methylation of tumor suppressor genes occurs in the early stage of carcinogenesis. Detecting risk factors for aberrant CpG methylation is clinically important for predicting cancer development. DNA methyltransferase (DNMT) 3a is considered to play critical roles in the DNA methylation process during pathogenesis. In this study, we evaluated the association between DNMT3A polymorphisms (rs6733868 and rs13428812) and CpG methylation status in non-cancerous gastric mucosa. Methods We determined the DNMT3A genotype and CpG methylation status of 4 genes (p14 ARF , p16 INK4a , DAPK, and CDH1) in 510 subjects without gastric cancer. Helicobacter pylori (HP) infection status was determined by the rapid urease test, urea breath test, speculum examination, or serum antibody test. We determined the DNMT3A genotype using polymerase chain reaction single-strand conformation polymorphism (PCR-SSCP). CpG methylation status was determined by methylation-specific polymerase chain reaction (MSP). When the methylated band was stronger than 10 ng/μL according to the DNA marker, we judged CpG island hypermethylation (CIHM) to be present. Associations between genotypes and susceptibilities were assessed by logistic regression analysis. Results The minor allele frequencies of both polymorphisms (rs6733868 and rs13428812) were lower in the CpG methylated groups of each of the 4 genes (p14 ARF , p16 INK4a , DAPK, and CDH1). Using a dominant genetic model, rs6733868 was significantly associated with the hypermethylation of each gene, whereas rs13428812 was associated with the methylation of 3 genes (all except p14 ARF ). When low-CIHM was defined as 1 or 2 CpG islands methylated and high-CIHM was defined as 3 or more CpG islands methylated, carrying the minor allele of rs6733868 was associated with both decreased low- and high-CIHM, and that of rs13428812 also was associated with a decrease. Comparing low-CIHM with high-CIHM, carrying the minor alleles of rs6733868 or rs13428812 was related to decreased susceptibility to high-CIHM. In HP-infected subjects, carrying the minor alleles of rs6733868 or rs13428812 had a significantly greater association with decreased susceptibility to high-CIHM. Conclusions Our study indicates that polymorphisms of DNMT3A are associated with the accumulation of gene methylation in gastric mucosa. Carrying the minor alleles of rs6733868 or rs13428812 inhibits aberrant gene methylations, which are typically enhanced by HP infection.